The Economic Valuation of Marjoly Beach and Resort Tour with Travel Cost Method (Travel Cost Method) Bintan District, Riau Islands Province - Handayani, Tri Dian; Warningsih, Trisla; Bathara, Lamun (Fakultas Perikanan dan Kelautan Universitas Riau, 2021)
This research was conducted at Marjoly Beach and Resort, Bintan Regency, Riau Islands Province. This study aims to describe the accommodation and entertainment as well as the socio-economic characteristics of visitors to Marjoly Beach and Resort, to analyze the factors that influence tourist visits to Marjoly Beach and Resort, to analyze the amount of economic value obtained by Marjoly Beach and Resort by accidental sampling with a total of 30 respondents. . The data needed in this research include primary and secondary data. Data were analyzed using descriptive analysis and multiple linear regression and from consumer surplus using the travel cost method. Respondents are determined using the travel cost method approach by estimating the economic value seen from the consumer surplus. The results showed that the total travel costs incurred by all visitors as respondents were around Rp. 38,035,000. Factors that influence tourist visits to Marjoly Beach and Resort are travel costs, income and age. The consumer surplus value obtained from the travel cost method is Rp. 50,276,669.60/ person per year or Rp. 17,955,953.4/ person per visit, then the total economic value obtained from assuming a surplus of tourism consumers in Marjoly Beach and Resort is Rp. 2,295,129,967.25.